The Opportunity of Implementation STEM Education Integrated with Language Teaching in Indonesian Elementary Schools - Ferril Irham Muzaki, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Education in Indonesia currently requires sufficient performance to improve abilities and skills in conducting critical discourse. To improve the ability, the performance of the community is needed to develop the characteristic values of each individual. With STEM Education in elementary schools, the existence of an education system that provides opportunities for the creation of humane learning and has character education values. The development of STEMbased character education values in elementary schools will be synchronized along with the development of information and communication technology which provides opportunities to develop character education values and nationalist insights. To develop this, STEM Education in elementary schools requires efforts to improve the skills and proficiency of an individual in terms of developing interests and identity. STEM Education can be taught in elementary schools in Indonesia, on extra-curricular materials such as robotics.